Where and Why in the UK? The Case of Polish Migrants - Kowalewska, Grażyna; Rutkowska-Ziarko, Anna; Simister, John; Sonmez, Yontem (Olsztyn Economic Journal, 2016)
This article focuses on one of the most controversial issues frequently discussed by many including politicians, academics and the media in the UK and Poland: migration of Polish people to Britain. The main aim is to identify the important factors causing migration of Poles within the UK. In this article, the authors seek to study the pull factors, i.e. level of wages or employment rate, for Polish people between different regions within the UK. By using the data from "Labour Force Surveys" collected by the UK government; and data from Główny Urząd Statystyczny (GUS) in Poland, this paper analyses where and why the Polish migrants live in the UK. The most important factor determining the fraction of Polish people in a given region is the fraction of Polish people in that region in the past. When Polish people move within UK, they tend to choose a region with a higher level of gross pay, and they don’t seem to consider the risk of unemployment. The authors are grateful to providers of survey data discussed in the "Data and methods" section of this paper. LFS data are made available by the UK Data Service. Views reported in this paper do not necessarily reflect opinions of organisations which commissioned or provided access to these surveys.